Pemahaman Ilmu Tajwid dan Kemampuan Menghafal Al-Quran di Pondok Pesantren Al-Hidayah Cibungbulang Kabupaten Bogor - Eda Laelasari; Maturidi Maturidi; Muhamad Sirojudin Abbas (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2021)
This study aims to: 1) obtain data on the understanding of the science of recitation of the santri at the Al-Hidayah Islamic Boarding School Cibungbulang, Bogor Regency; 2) obtaining data on the ability to memorize the Al-Quran of Santri at Al-Hidayah Islamic Boarding School Cibungbulang, Bogor Regency; 3) find out the correlation between the understanding of tajwid and the ability to memorize Al-Quran of students at the Al-Hidayah Islamic boarding school, Cibungbulang, Bogor Regency. The total research population is 100 people. Samples were taken using a simple random sample technique of 30 respondents. The research approach uses quantitative methods. The technique of collecting data used a written test and a practical test. Data analysis technique, to determine the correlation of variable X (understanding of tajwid science) with variable Y (ability to memorize Al-Quran) using Pearson Product Moment correlation test technique. The calculated r index is 0.703, which is greater than r table = 0.361, which is significant. This means that the understanding of tajwid has a correlation with the ability to memorize the Qur'an. The KD index (Determinant Coefficient) is 49.42% which indicates that the X variable (understanding of recitation science) contributes 42.12% to the Y variable (the ability to memorize the Quran), and the remaining 50.58% is determined by other factors .